2020
DOI: 10.3390/ijerph17176404
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Positive Youth Development and Depressive Symptoms among Chinese Early Adolescents: A Three-Year Cross-Lagged Analysis

Abstract: Based on the development assets theory and the scar model, the present study examined the relationship between positive youth development (PYD) and depressive symptoms among Chinese early adolescents using a three-year longitudinal study design. Data from three waves were collected from 1301 students (Mean age = 12.46, SD = 0.63 years and 51.2% boys at wave 1) across the junior high school period (Grades 7–9). All participants completed a questionnaire that included the Center for Epidemiologic Studies Depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…Several reasons for the development trend of adolescent depressive symptoms are as follows. During Grade 7 to Grade 8, students have to adapt to the new peers and new teachers as well as confront the challenges of self-development tasks like self-identity confusion (67), so the depressive symptoms are relatively high. After entering Grade 9, apart from the special attention on entrance examination that makes adolescents regulate their mood to concentrate on learning, the matures of physical and mental development may also contribute to the natural decrease of mild or moderate depressive symptoms in adolescents (68).…”
Section: Discussionmentioning
confidence: 99%
“…Several reasons for the development trend of adolescent depressive symptoms are as follows. During Grade 7 to Grade 8, students have to adapt to the new peers and new teachers as well as confront the challenges of self-development tasks like self-identity confusion (67), so the depressive symptoms are relatively high. After entering Grade 9, apart from the special attention on entrance examination that makes adolescents regulate their mood to concentrate on learning, the matures of physical and mental development may also contribute to the natural decrease of mild or moderate depressive symptoms in adolescents (68).…”
Section: Discussionmentioning
confidence: 99%
“…The higher the mean score, the higher the level of depression among teenagers. In previous studies, this scale also showed great reliability and validity [ 34 , 51 ]. In this study, Cronbach’s alpha for the CES-D was 0.90.…”
Section: Methodsmentioning
confidence: 87%
“…For example, Milot Travers and Mahalik [ 33 ] found that lower levels of PYD attributes were significantly linked to a higher prevalence of depression among teenagers. A three-year longitudinal study has revealed that PYD is a negative predictor of future depressive symptoms [ 34 ]. Besides, a two-wave design study also indicated that higher PYD attributes predicted a drop in Chinese adolescent depression both concurrently and longitudinally [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…A higher mean score indicated a more severe depressive symptom. This measure demonstrated good reliability and validity among Chinese adolescents ( 49 ). In this research, Cronbach's alpha values of this scale at T1, T2, and T3 were 0.853, 0.877, and 0.886, respectively.…”
Section: Methodsmentioning
confidence: 95%